2020
DOI: 10.1002/ajim.23088
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and oxidative stress biomarkers induced by silica exposure in crystal craftsmen

Abstract: Background Identification of biomarkers associated with the diagnosis and prognosis of silicosis would be highly advantageous in the clinical setting. The aim of this study is to evaluate inflammatory and oxidative stress biomarkers in subjects exposed to silica. Methods A cross‐sectional study of crystal craftsmen currently (n = 34) or formerly (n = 35) exposed and a group of nonexposed subjects (n = 12) was performed. Personal respirable dust samples were collected. Plasma inflammatory mediators (bone morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
8
1
2
Order By: Relevance
“…Previous research has described increased levels of inflammatory serum markers in silica exposed subjects 8 , 15 . It has been observed that the presence of different polymorphisms, alongside with TNF, IL-1RA and TGF-β1 16 – 18 confer a higher risk of disease, and that levels of TNF-α show an increase before the development of a clinically recognised silicosis 19 and that are associated with disease severity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research has described increased levels of inflammatory serum markers in silica exposed subjects 8 , 15 . It has been observed that the presence of different polymorphisms, alongside with TNF, IL-1RA and TGF-β1 16 – 18 confer a higher risk of disease, and that levels of TNF-α show an increase before the development of a clinically recognised silicosis 19 and that are associated with disease severity.…”
Section: Discussionmentioning
confidence: 94%
“…Once the disease is contracted, silicosis can evolve to cause important morbidity and mortality, even after exposure is ceased. To date, different potential biomarkers have been suggested 8 but the lack of definitive results precludes use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that, even in individuals with relevant exposure and ILO category 0 radiographs, CT classification of nodules was able to capture the presence of silicosis, which was supported by a dose–response gradient. Likewise, improved understanding of the basic pathophysiology of silicosis and the role of many cytokines, chemokines and other mediators involved in pulmonary fibrotic response,27 35 along with modern imaging techniques, may improve the recognition of early signs of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Las NPs de muy baja biosolubilidad como SiO2, CeO2, ZrO2, y asbestos pueden destruir a estas células liberando enzimas y ROS. Esto genera citoquinas inflamatorias y fibróticas, causando daños en el tejido [28]. En resumen, se han identificado varios procesos de daño toxicológico, sin embargo, los mecanismos completos que subyacen a ciertos hallazgos toxicológicos aún no se comprenden del todo y siguen siendo objeto de intensa investigación.…”
Section: Implicaciones En La Salud Humanaunclassified